Система надання рекомендацій з догляду за кімнатними рослинами - Басюк, Тарас; Пелех, Анастасія (Видавництво Львівської політехніки, 2017)
The article is devoted to creation of system of provision of advice on the care of houseplants, which from an aesthetic point of view, improve the lives of people seeking homes that strive to achieve the "green comfort". The paper presents the description of the designed system, which provides tips on caring for house plants, contains useful articles and the forum has a convenient search by type of plant.
Keywords: квітникарство; кімнатні рослини; надання рекомендацій; догляд